Heart rate variability measures indicating sex differences in autonomic regulation during anxiety-like behavior in rats - Frasier, Raizel M.; De Oliveira Sergio, Thatiane; Starski, Phillip A.; Grippo, Angela J.; Hopf, F. Woodward (Frontiers in Psychiatry, 2023)
Mental health conditions remain a substantial and costly challenge to society, especially in women since they have nearly twice the prevalence of anxiety disorders. However, critical mechanisms underlying sex differences remain incompletely understood. Measures of cardiac function, including heart rate (HR) and HR variability (HRV), reflect balance between sympathetic (SNS) and parasympathetic (PNS) systems and are potential biomarkers for pathological states. To better understand sex differences in anxiety-related autonomic mechanisms, we examined HR/HRV telemetry in food-restricted adult rats during novelty suppression of feeding (NSF), with conflict between food under bright light in the arena center.To assess HRV, we calculated the SDNN (reflective of both SNS and PNS contribution) and rMSSD (reflective of PNS contribution) and compared these metrics to behaviors within the anxiety task. Females had greater HR and lower SNS indicators at baseline, as in humans.Further, females (but not males) with higher basal HR carried this state into NSF, delaying first approach to center. In contrast, males with lower SNS measures approached and spent more time in the brightly-lit center. Further, females with lower SNS indicators consumed significantly more food. In males, a high-SNS subpopulation consumed no food. Among consumers, males with greater SNS ate more food. Together, these are congruent with human findings suggesting women engage PNS more, and men SNS more. Our previous behavior-only work also observed female differences from males during initial movement and food intake. Thus, high basal SNS in females reduced behavior early in NSF, while subsequent reduced SNS allowed greater food intake. In males, lower SNS increased engagement with arena center, but greater SNS predicted higher consumption. Our findings show novel and likely clinically relevant sex differences in HRV-behavior relationships.